Influence of crowd size on home advantage in the Japanese football league - Nomura, Ryota (Frontiers in Sports and Active Living, 2022)
This study aimed to investigate the influence of crowd size on home advantage (HA). Data of the 2019 and 2020 seasons of the J1 League (Japan Professional Football’s First Division League) were analysed. Matches during the 2019 season were played under regular conditions, while there was low stadium occupancy during the 2020 season to prevent the spread of COVID-19. Regarding average points won, HA disappeared. By using multiple group structural equation modelling, it was examined the routes of influence via which a reduction in crowd size influenced HA. The results indicated that the influence from the crowd size to the referee’s decisions disappeared during the 2020 season. However, the factors including the referee’s decisions have lower effects on the outcome factor. Hence, no dominant route was detected in the present study.